In vitro fermentation characteristics of dietary fibers using fecal inocula from dogs fed a canned diet and treated with metronidazole - Martini, Sara E.; Oba, Patrícia M.; Geary, Elizabeth L.; Bauer, Laura L.; Dilger, Ryan N.; Swanson, Kelly S. (Frontiers in Veterinary Science, 2025)
IntroductionMetronidazole is a potent antibiotic often prescribed to treat gastrointestinal enteropathies; however, it is known to induce loose stools, negatively alter the fecal microbiome, and affect fecal metabolite production. Dietary intervention may aid in post-antibiotic recovery; however, little research has been conducted on the potential of fiber utilization for microbial recovery in canines.MethodsUsing an in vitro fermentation assay, the objective of this study is to investigate the fermentation characteristics of dietary fibers using fecal inocula from dogs treated with metronidazole. Four healthy male beagles (age = 1.62 ± 0.02 year) were fed a commercial canned diet for 2 weeks, then administered metronidazole (20 mg/kg BW BID) for 2 weeks. Fresh fecal samples were collected at weeks 2 (before antibiotic treatment; ABX−) and 4 (after antibiotic treatment; ABX+), stabilized in a 20% glycerol solution, and then frozen. On the day of in vitro fermentation, feces from each time point were thawed and used to inoculate the tubes. At baseline and after 6, 12, and 18 h of fermentation, pH, short-chain fatty acids (SCFA), and microbiota were measured. Blank-corrected changes from the baseline data were analyzed using repeated measures and the MIXED procedure in SAS 9.4, with significance set at a p value <0.05.ResultsPectin fermentation reduced (p < 0.001) pH and increased (p < 0.001) SCFA over time, but the responses were lower (p < 0.001) in ABX+ than in ABX−. Beet pulp fermentation also reduced (p < 0.001) pH and increased (p < 0.001) SCFA over time. The pH change was small between inoculum sources, but SCFA were different (p < 0.001) between ABX+ and ABX−. Chicory pulp fermentation reduced (p < 0.001) pH over time, with greater (p < 0.01) reductions in ABX+ than in ABX−. Chicory pulp fermentation increased SCFA but had different patterns depending on the inoculum source. Metronidazole altered microbiota populations by reducing bacterial alpha diversity (p < 0.001). Analysis of bacterial beta diversity revealed separate clusters in dogs based on metronidazole administration. Beta diversity analysis also showed that tubes containing chicory pulp clustered separately from those containing other fibers. The relative abundance of over 50 bacterial genera differed (p < 0.05) among the inoculum sources.DiscussionIn summary, interesting fermentation patterns were observed in response to varying fiber sources, allowing for improved insights into their potential abilities in antibiotic-treated dogs.